ICT BASED PLANETARIUM WITH EDUTAINMENT APPROACH IN MALANG CITY - Febryanti, Berliana (Jurnal Mahasiswa Departemen Arsitektur, 2025)
Malang, with an area of 145.28 km² and the motto "Tri Bina Cita," has significant potential as a center for education, industry, and tourism. One promising innovation for developing the tourism sector is the creation of an edutainment-based planetarium. This planetarium would integrate advanced technology to offer an interactive and educational experience, particularly in support of STEM (Science, Technology, Engineering, and Mathematics) education. Kedungkandang, with its growing accessibility and infrastructure, is considered a strategic location for this planetarium. This design proposal examines the potential for a planetarium in Malang, focusing on the concept of educational tourism and technology. By applying a rationalism paradigm with a precedent study method, an analysis is conducted to establish a suitable design foundation (Rules of Assembly). The design results show that applying a rationalist approach to architectural design, combined with the concept of edutainment, can enhance the learning experience and become a modern tourist attraction. This design also has the potential to support local economic growth through education-based tourism development in Kedungkandang.